Cutaneous apocrine gland neoplasia in 16 captive African wild dogs (Lycaon pictus) - (:unkn) unknown (My University, 2023)
This retrospective study documents the occurrence of single and multiple cutaneous apocrine gland tumours (CATs) on the dorsal midline of 16 captive African wild dogs (AWDs, Lycaon pictus) derived from 161 submissions to diagnostic laboratories in South Africa, France and Germany between 1997 and 2022. Animals included in the study came from zoological institutions in South Africa (n ¼ 2), France (n ¼ 5) and Germany (n ¼ 1) and ranged from 5 to 14 years of age. Fifteen affected animals were female (94%) and one was male. CATs presented as raised, hairless, multilobular, grey firm masses, consistently located along the dorsal midline. Apart from a single cutaneous apocrine adenoma and a cystadenoma occurring concurrently with two non-cystic adenocarcinomas, neoplasms were consistent with malignant cuta- neous apocrine adenocarcinomas with lymphatic spread and visceral metastases. Advanced age and female sex were identified as risk factors. A genetic component or association with the increasing use of GnRH agonist contraceptives was suspected but could not be established. This study highlights the need for close clinical monitoring of AWDs over the age of 5 years for the development of CATs along the dorsal midline and supports early surgical intervention. More research is needed to determine the role of inbreeding, endocrine changes and husbandry factors that may play a role in the development of CATs on the dorsal midline of AWDs.
Keywords: African Research